Increasing The Students’ Ability In Writing Skill By Using IBC Strategy - Hidayati Daeli; Afore Tahir Harefa; Hasrat Sozanolo Harefa (Departement of Mathematics Education, 2022)
Writing is an ability to express the idea or thought to the other in written form. In writing, the students has to be able to express his/her thought in writing in order that the reader can understand and get message easily. In the syllabus of curiculum 2013 at the eleventh grade of SMA Negeri 1 Hiliduho expected the students were able to express the meaning in short functional text and simple short essay in the form of recount. In fact, the students are unable to realize what the syllabus hope, so they could not achieve the target of MCC in writing. In solving the problem, the researcher tries to increase the students’ ability in writing paragraph especially in recount text by using IBC strategy by designing Classroom Action Research in teaching learning process. The subject of this research is the students of the eleventh grade of SMA Negeri 1 Hiliduho which is the total number of the students is 30 students. The research was applied in two cycles, each cycles consist of two meetings. Each meeting followed the steps of CAR: planning, action, observation and reflection. In collecting the data of the students’ ability in writing recount text by using IBC strategy, the researher use observation papers, field notes, writing test, and camera. Cycle I in first meeting, the students’ observation paper showed that there were 10 students (33,34%) had done all of the activities and 20 students (66,66%) had not done the activities; the second meeting, there were 14 students (46,67%) had done all the activities and 16 students (53,33%) had not done the whole activities; and the result of the students’ evaluation paper showed that there are 3 students (10%) in very good level, 2 students (6,67%) in good level, 8 students (26,66%) in enough level, 15 students (50%) in less level and 2 students (6,67%) in fail level. Then, the average of the students’ value is 58,5. This mean noted that the students still less in achieving MCC 60. In cycle II, the researcher re-planed and improved the weaknesses of the activities of the cycle I in order that the students’ ability could achieve the MCC 60. The result of the students’ evaluation paper in first meeting showed that there are 25 students (83,33%) had done all the activities and 5 students (16,67%) had not done all the activities; in the second meeting there were 29 students (96,67%) had done the activities and 1 student (3,33%) had not done the whole activities; and the result of the students’ evaluation paper stated that there were 15 students (50%) in very good level, 12 students (40%) in Good level and 3 students (10%) in enough level. It showed that all the students achieved MCC is 60. The average of the students’ value is 82,3. This value said that the students’ ability in writing recount text by using IBC strategy was increased effeciently and effectivelly. The researcher had some suggestions, such as: IBC strategy is effective used by English teacher in teaching writing recount text because it interests, encourage, and motivates the students in writing, the students should often practice to write English trainning them to have writing English habit, the English teacher needs to motivate the students to convey their opinions and ideas in writing form, and be active using dictionary.